NEMATICIDAL PROPERTIES OF SOME MEDICINAL PLANTS FROM SELECTED FLORA OF GILGIT-BALTISTAN - M. Ismail; S. Fayyaz; M. Azad; S. Javed; I. Ali; S. Ali; S. Hussain (Journal of Animal and Plant Sciences, 2019)
Man is interested in plants for the treatment of diseases from prehistoric times. Medicinal plants have great importance in treatment of different diseases. Pesticides are beneficial for crop protection, food preservation, disease control as well as it is risk for human health, ill impact on environment and ecosystem. Different plant species are considered to possess the toxicity against various nematodes and used as green alternatives to conventional harmful organophosphorus and carbamates. The main objective of the current study is to evaluate the nematicidal properties of Peganum harmala, Clematis orientalis, Mentha longifolia, and Capparis spinosa from Gilgit-Baltistan region of Pakistan against root-knot nematodes. The polar and non-polar extracts of these plant species were assessed to study the nematicidal effects against Meloidogyne incognita. The effect of 0.125, 0.5, and 1% methanolic, ethyl acetate, aqueous, and n-hexane extracts of these plantsexhibited highly promising nematicidal activity (47-75% mortality) after 72 h of treatment. The 1% solution of methanolic extracts of C. orientalis, P. harmala, and C. spinosa were found to be the most active fractions that exhibited 75, 71, and 75% mortality, respectively after 72 h. At this concentration conventional nematicide furadan showed 100% mortality. It was concluded that the tested plants furnished a good option to control nematodes as green alternatives to conventional practices.
Keywords: Capparis spinosa; Clematis orientalis; Mentha longifolia; Peganum harmala; root-knot nematode; green